Freely Selective Analog and Digital Resistive Switching Behavior of In2Se3 Devices for Storage and Neuromorphic Applications - Siying Tian; Changhao Wang; Yuanjie Wang; Honghao Wang; Chenxi Gao; Weisen Hu; Jia Wei; Fengling Chen; Dapeng Sun; Xu Zheng; Chaobo Li; Chujun Yin (Advanced Electronic Materials)
Abstract Digital storage and analog storage shine in different fields mainly due to their strong stability and high information density, respectively, while the freely selective digital and analog resistance switching applications are a matter of great concern. Here, a multi‐functional device integrated with analog and digital resistive switching behavior in a simple structure is reported, achieving functions of freely selective non‐volatile digital storage, artificial synaptic behavior based on ferroelectric polarization‐inducing analog resistive switching behavior, neural network computing, and reconfigurable logic functions. The non‐volatile digital memory exhibits a low operating voltage (≈1—2 V) and high retention stability (> 2000 s). The analog resistive switching behavior exhibits 128‐level conductance and excellent artificial synaptic performance with a large dynamic range (≈196), high linearity (≈0.84), and low power consumption. The modulation effect of band bending, an often underappreciated yet crucial element, is considered to analyze the mechanisms behind the optimized device performance, further providing support and expansion for the multifunctional applications of In2Se3 devices. Reconfigurable logic functions and an artificial neural network (ANN) with outline learning accuracy (≈89%) for handwritten digit recognition are achieved. This design provides new insights into the analysis of 2D ferroelectric devices and holds great promise for simplified and multi‐functional storage‐computing devices.